Ethical Considerations in Artificial Intelligence A Framework for Responsible Information Systems Development - Alfina (Journal Informatic, Education and Management (JIEM), 2024)
This research aims to develop a framework that explains ethical considerations in the responsible development of Information Systems (IS) related to artificial intelligence (AI). The research method used involved a thorough literature review to identify relevant ethical principles in the context of AI and IS. Apart from that, an in-depth analysis of various existing models and frameworks was also carried out to understand ethical considerations in technology development. The result of this research is a framework consisting of a series of ethical principles that must be considered at every stage of IS development that uses AI technology. This framework considers not only the technical aspects of system development, but also relevant social, legal and cultural aspects. Through the application of this framework, IS developers can ensure that the resulting products are not only of high technical quality, but also pay attention to their impact on individuals, society and the environment. The conclusions of this research emphasize the importance of including ethical considerations as an integral part of the IS development process that uses AI to achieve the goals of socially responsible technology development.